Epidermal acantholysis induced in vitro by pemphigus autoantibody. An ultrastructural study. - Hu, C. H. (1978)
Suprabasilar acantholysis can be produced in organ culture of normal human skin in the presence of pemphigus IgG autoantibody. We have examined this in vitro system by electron microscopy. The earliest ultrastructural changes at 12 hours included widening of the intercellular spaces and disruption of the intercellular cement substance in the nondesmosomal areas. After 24 to 48 hours in culture, the tonofilaments retracted from the cell periphery, desmosomes were lost, and extensive cell surface digitation occurred. By 72 hours, isolated cells without noticeable desmosomes were seen in the suprabasilar areas, whereas basal cells, with intact hemidesmosomes, remained attached to the basal lamina. Control cultures which were grown in the presence of normal IgG or F-10 medium alone did not manifest these changes. The ultrastructural features support the conclusion that the acantholysis produced in this system is similar and probably identical to that of naturally occurring pemphigus.